Hydroisomerization of n-hexadecane using Pt/alumina-Beta zeolite catalysts for producing renewable diesel with low pour point. (1st December 2017) - Gomes, Luis Carlos; de Oliveira Rosas, Danielle; Chistone, Rodrigo Caetano; Zotin, Fatima M. Zanon; de Araujo, Lucia R. Raddi; Zotin, José L.
Graphical abstract: Highlights: Pt/Alumina-Beta (Si/Al = 150) was evaluated on n-C16 hydroisomerization. Product distribution is independent of the zeolite content. A relation between the first order kinetic constant and total acidity was found. These catalysts showed performance comparable with shape selective zeolites. Pour point correlates with primary and secondary carbon contents of the products. Abstract: The performance of bifunctional Pt/Alumina-Beta zeolite catalysts for the hydroisomerization (HDI) of n-C16 was studied by varying the zeolite content in the support. A relationship between overall activity and support acidity was observed, indicating that the skeletal isomerization over zeolite acid sites is the rate-determining step. Isomerization and cracking products distributions are independent of the zeolite content in the support for the entire range of n-C16 conversion. The catalysts of the present study are more selective than those previously reported in the literature with Beta zeolite, which is probably associated to the use of a high Si/Al zeolite. Finally, it was observed that the pour point of the hydroisomerized products decreases with the overall conversion and correlates with the primary and secondary carbon contents of the products.